Penggelapan Dana Indonesia Pintar: Ancaman Serius bagi Hak Pendidikan Anak Bangsa - Annisa Nur Hanifah; Hasna Yunihanifah; Yunita Nur Rahmawati; Mozart Tiasylva Syah Nuhandika; Kanaya Ayodya Indra Prasta; Nurlaily Fauziaturrina (Majelis: Jurnal Hukum Indonesia, 2026)
The Indonesia Pintar Program (PIP) serves as a strategic state instrument to ensure equitable access to education for children from low-income families, in accordance with the constitutional mandate. However, the prevalence of fund embezzlement poses a severe threat to the fulfillment of these educational rights. This study aims to analyze the structural and institutional dynamics triggering fund misappropriation, evaluate the effectiveness of current oversight mechanisms, and formulate strategies to mitigate such violations. This research employs a normative legal method with a descriptive-analytical approach, utilizing statutory and socio-legal analysis to examine regulations such as Law No. 20 of 2003 and relevant ministerial decrees. The findings reveal that embezzlement is driven by complex structural factors, including data asymmetry between Dapodik and DTKS, weak internal supervision, and a lack of transparency in fund distribution. Furthermore, legal enforcement remains suboptimal, often limited to administrative sanctions due to difficulties in proving mens rea and poor coordination among law enforcement agencies. The study concludes that current oversight mechanisms are insufficient to curb corruption in the education sector. Therefore, comprehensive reform is urgently needed, focusing on the integration of digital data systems, the implementation of e-audits, and the enhancement of civil society participation to ensure accountability. These measures are essential to protect the constitutional rights of children and ensure that education funds reach their intended beneficiaries without leakage.